Modeling of anisotropic behavior to investigate the effect of hardness on AA2014 aluminum alloys under upsetting. (November 2018) - HariKrishna, Ch.; Davidson, MJ; Nagaraju, Ch.; Srinivasa Rao, G; Srinivasa Raju, P
The hardness of the metals in the bulk forming operations, such as upsetting increases, when the material is compressed. The increase in the level of strain improves the hardness of the billets in the upsetting tests. Issues like anisotropy may arise depending on the class of material and effect of the anisotropy on the metallic hardness is an interesting study for the effective utilization of material. Three sets of AA2014 billets solutionized at 502 ℃ and aged for 9 h, 13 h, and 18 h at a temperature of 150 ℃ were considered for the investigation. The effect of the material constant ( C 1 ) on the variations in hardness was studied. Billets aged for 18 h were upset by employing three different lubricants namely grease, molybdenum disulphide, and white grease to study the effect of lubrication on anisotropy. The effect of anisotropy on hardness was studied by modeling Hill's criteria for anisotropy with the hardness. The empirical results of hardness values were compared with the values of experimental hardness for validity.